The gendered impacts of agricultural asset transfer projects: Lessons from the Manica Smallholder Dairy Development Program - Johnson, Nancy L.; Njuki, Jemimah; Waithanji, Elizabeth M.; Nhambeto, Marinho; Rogers, Martha; Kruger, Elizabeth Hutchinson (International Food Policy Research Institute, 2013)
This paper looks at the gendered impacts of a development project that provided improved dairy cattle and training as part of a broader effort to develop a smallholder-friendly, market-oriented dairy value chain in Manica province, Mozambique. The project targeted households, registered cows in the name of the household head, and, initially, trained registered cow owners in various aspects of dairy production and marketing. Subsequently training was expanded to two members per household to increase the capacity within households to care for cows, a change which resulted in a significant number of women being trained.